THE EFFECTS OF PARENTING STYLES ON ACADEMIC ACHIEVEMENT AND SCHOOL ADJUSTMENT AMONG HIGH SCHOOL STUDENTS IN NAGALAND, INDIA: THE MEDIATING EFFECTS OF ATTACHMENT DIMENSIONS, ACADEMIC SELF-EFFICACY AND EMOTIONAL REGULATION - Mohanan, Dr. Santhosh Ayathupady; George, Pezalhoukho (Scholar: Human Sciences, 2022)
The present study attempted to examine the mediating effects of adolescent attachment, emotional regulation and academic self-efficacy between parenting styles, academic achievement, and school adjustment among high school students in Nagaland, India. Furthermore, it investigated whether the structure of direct and indirect structural relationships hypothesized varies as a function of their parents’ genders. The participants of this study were high school students from Nagaland, India. The questionnaire consisted of the following scales: Parenting Authority Scale, Adolescent Attachment Questionnaire, Academic Self-efficacy Scale, Difficulties in Emotion Regulation Scale, College Adjustment Test and GPA. In order to meet the study’s objectives, three studies were designed and conducted via SEM and AMOS with the purpose to investigate the direct and indirect effects of parenting styles on academic achievement and school adjustment among high school students in Nagaland, India: the mediating effects of attachment dimensions, academic self-efficacy, and emotional regulation. The results revealed that authoritarian parenting style had direct correlation with academic achievement and that authoritarian and permissive parenting styles had indirectly effect on school adjustment mediated by adolescent attachment and emotional regulation. The pattern of structural relationships hypothesized for the proposed model parenting styles the result found it operate differently for fathers and mothers. There were neither direct nor indirect correlation between the predictor and the outcome in the case of the fathers parenting style in this sample group. But in the case of the mother, authoritarian parenting style had direct significant correlation with academic achievement and significant correlation between school adjustment and lack of angry distress, goal-corrected partnership, and emotional regulation. The study’s limitations, implications, and future avenues were also discussed.